2022
DOI: 10.1097/cad.0000000000001273
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine improves the outcomes of regorafenib in metastatic colorectal cancer

Abstract: Regorafenib is a multikinase inhibitor. It is used for metastatic colorectal cancer (mCRC) treatment. It has a mild effect. Regorafenib outcomes, and side effects may vary across patients. This study was aimed to evaluate the factors that affect regorafenib outcomes in mCRC patients. We conducted a single-center and retrospective study. Fifty-six patients were included. All patients had received regorafenib for mCRC. Some clinical and pathological factors and the effects of these factors on overall survival (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Amlodipine has a special place among repuposed molecules in cancer treatment. In our previous retrospective studies, we have shown that especially regorafenib and amlodipine combination increases the effectiveness at colorectal cancer [2]. In out another study, we showed that amlodipine inproves outcomes of erlotinib in non-small cell lung cancer [3].…”
Section: Introductionmentioning
confidence: 85%
“…Amlodipine has a special place among repuposed molecules in cancer treatment. In our previous retrospective studies, we have shown that especially regorafenib and amlodipine combination increases the effectiveness at colorectal cancer [2]. In out another study, we showed that amlodipine inproves outcomes of erlotinib in non-small cell lung cancer [3].…”
Section: Introductionmentioning
confidence: 85%
“…Recently, the CCB amlodipine (commonly used to treat arterial hypertension) was found to markedly enhance the therapeutic response to gemcitabine chemotherapy in pancreatic cancer, extending survival and reducing the risk of distant metastases [ 53 ]. In addition, the drug was found to enhance the response to the multikinase inhibitor regorafenib in patients with metastatic colorectal cancer [ 54 ]. Several in vitro/in vivo studies have revealed that amlodipine, lercanidipine, and other structurally related CCBs can exert an antiproliferative action toward cancer cells and/or promote the efficacy of different anticancer drugs [ 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Drug Repositioning To Target the Pd-1/pd-l1 Checkpointmentioning
confidence: 99%